(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to describe the description of public trust and the stages of the science of pesugihan parakang in the novel Natisha by Khrisna Pabichara. This study focuses on the public’s belief in the science of pesugihan parakang and the stages of the science of pesugihan parakang in the novel Natisha. This type of research is library research or literature review, namely the technique of collecting data through the library. In this study, a qualitative approach was used, namely describing the sentences resulting from the data in the form of sentences in novels which were classified based on the description of public trust and the stages of the science of pesugihan parakang. The results in this study found that people in the past, long before Islam was present, they believed in the existence of pesugihan parakang science. This is evidenced by the data found in the description of public trust and the stages of Parakang pesugihan science with a total of nineteen data.